Invisible girl : [large type] a novel - Jewell, Lisa (Thorndike Press, a part of Gale, a Cengage Company, 2020)
"Owen Pick's life is falling apart. He's thirty-three, a virgin, and has just been suspended from his teaching job after accusations of sexual misconduct. He then discovers the dark world of incel--involuntary celibate--online forums and meets the mysterious and sinister Bryn. Across the street from Owen lives the Fours family, who have a bad feeling about their neighbor. Meanwhile, young Saffyre Maddox spent three years as a patient of Roan Fours, a child psychologist. Feeling abandoned when their therapy ends, she tries to maintain her connection with him. Then, on Valentine's night, Saffyre Maddox disappears--and the last person to see her alive is Owen Pick"--Page 4 of cover.